2021
DOI: 10.1093/emph/eoaa051
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing

Abstract: Background There has been an increased usage of metallic antimicrobial materials to control pathogenic and multidrug resistant bacteria. Yet, there is a corresponding need to know if this usage leads to genetic adaptations that could produce more harmful strains. Methodology Experimental evolution was used to adapt Escherichia coli K-12 MG1655 to excess iron (II) with subsequent genomic analysis. Phenotypic assays and gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In addition, we found that iron (II)-and iron (III)-resistant populations showed unanticipated correlated resistances to a range of antibiotics including ampicillin, chloramphenicol, rifampicin, sulfanilamide, and tetracycline. Our results suggested that E. coli K-12 could respond to excess iron by both physiological acclimation and evolutionary adaptation [13]. This was manifested by both patterns of genomic and gene expression changes exhibited in the iron (II)-, iron (III)-, and Gallium (III)-resistant populations compared to their ancestors and controls (grown in the absence of excess iron or gallium).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, we found that iron (II)-and iron (III)-resistant populations showed unanticipated correlated resistances to a range of antibiotics including ampicillin, chloramphenicol, rifampicin, sulfanilamide, and tetracycline. Our results suggested that E. coli K-12 could respond to excess iron by both physiological acclimation and evolutionary adaptation [13]. This was manifested by both patterns of genomic and gene expression changes exhibited in the iron (II)-, iron (III)-, and Gallium (III)-resistant populations compared to their ancestors and controls (grown in the absence of excess iron or gallium).…”
Section: Introductionmentioning
confidence: 73%
“…In addition, if they can, what correlated traits will result from the adaptation? We have already answered some of these questions in a series of experiments utilizing ionic iron II, iron III, and the iron analog gallium III [13][14][15]. These studies utilized experimental evolution and examined mechanisms of iron and gallium resistance through the evaluation of phenotypic and genomic changes in E. coli K-12 MG1655.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that E. coli K-12 could respond to excess iron by both physiological acclimation and evolutionary adaptation [13]. This was manifested by both patterns of genomic and gene expression changes exhibited in the iron (II), iron (III), and Gallium (III)-resistant populations compared to their ancestors and controls (grown in the absence of excess iron or gallium).…”
Section: Introductionmentioning
confidence: 73%
“…Bacterial strains E. coli MG1655 (ATCC #47076) was used in this study because it does not have plasmids and its circular chromosome is composed of 4,641,652 nucleotides (GenBank: NC_000913.3; Riley et al 2006). All of our previous studies of ionic and nanoparticle resistance have used this strain [13][14][15]. This strain is the ancestor of all the selection treatments (FeNP and Controls) evaluated in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation